E-COMMERCE IN INDIA: EMERGING TRENDS AND WAY FORWARD (International Journal of Food and Nutritional Sciences, 2022)
What we call "e-commerce" (or "e-commerce") is the practice of buying and selling products and services over the Internet, along with the associated transmission of information and money. Shopping online is what most people think of when they hear that phrase. The growth of India's online retail sector is astounding. E-commerce is unquestionably a business option that should be considered in the future.